Nanosecond Nd: YAG Laser Surface Cleaning of Metals and Marbles - Ibrahim, Hanan I.; Hamoudi, Walid K.; Edan, Mehdi Salih (Iraqi Journal of Laser, 2019)
Laser cleaning of materials’ surfaces implies the removal of deposited pollutants without affecting the material. Nanosecond Nd:YAG pulsed laser, operating at 1064 nm and 532nm, was utilized. Different laser intensities and number of pulses were used on metallic and non-metallic surfaces under O2 and Ar environments to remove metal oxide and crust. Cleaning efficiency was studied by optical microscope. The results indicated the superiority of 1064 nm over the 532 nm wavelength without any detectable damage to materials’ surfaces. Marble cleaned in Oxygen gas environment was better than in Ar gas.